Tuberculosis Peritonitis During Treatment of Polycythemia Vera with Ruxolitinib - Sakiyama E (Infection and Drug Resistance, 2020)
Emiko Sakiyama, Yoshiaki Chinen, Taku Tsukamoto, Tomoko Takimoto-Shimomura, Saeko Kuwahara-Ota, Yayoi Matsumura-Kimoto, Yuji Shimura, Tsutomu Kobayashi, Shigeo Horiike, Junya Kuroda Division of Hematology and Oncology, Department of Medicine, Kyoto Prefectural University of Medicine, Kyoto, JapanCorrespondence: Junya Kuroda Email junkuro@koto.kpu-m.ac.jpAbstract: Ruxolitinib is a selective JAK1/2 inhibitor that is widely used for the treatment of myeloproliferative neoplasms (MPNs), including myelofibrosis and polycythemia vera (PV). Despite its clinical efficacy for MPNs, ruxolitinib possesses immunosuppressive properties that potentially increase the risks for opportunistic infection, such as mycobacterium tuberculosis (MTB) infection, and reactivation of occult viral infection. Herein, we report the case of a 76-year-old male with PV who developed tuberculosis peritonitis under ruxolitinib therapy for 28 weeks. While previous studies and case reports have suggested an increased risk of MTB infection of various organs during ruxolitinib treatment of MPNs, this case is apparently the first of tuberculosis peritonitis in a patient with MPN treated with ruxolitinib. A review of previous case reports suggests the need for careful observation for MTB from the relatively early phase of ruxolitinib treatment, given that the median duration from the start of ruxolitinib treatment to the emergence of MTB was 20 weeks (range: 3– 88 weeks). Clinicians should consider tuberculosis peritonitis as a differential diagnosis when patients with MPN treated with ruxolitinib develop infectious abdominal symptoms.Keywords: ruxolitinib, tuberculosis peritonitis, polycythemia vera